Google and Corporate Social Responsibility: youTube in the Service of Terrorism - Kōhēn-Almagôr, Refaʾēl (Perspectives on terrorism, 2022)
This article is concerned with the boundaries of freedom of expression on the Internet and, more specifically, with manifestations of terrorism on YouTube. The article opens with two definitions of terrorism. Section II discusses various responsibilities that businesses have: economic, legal, moral, social and discretionary. Section III addresses the concept of Corporate Social Responsibility (CSR). Unfortunately, not all companies adhere to the principles of Corporate Social Responsibility. Therefore, ethical standards should be anchored in appropriate laws and enforced by responsible governments. Section IV clarifies that incitement to violence is in the focus of attention. The philosophy of John Stuart Mill is instrumental in explaining the difference between advocacy (or preaching) and incitement (or instigation). Sections V and VI examine the influences of Anwar al-Awlaki, the American-Muslim jihadi preacher, and of Anjem Choudary, the British-Muslim jihadi preacher, on their followers. The words of al-Awlaki and of Choudary instigated many of the terrorist activities that the West had seen in recent years. There are direct links between their incitement and extreme violent incidents. Both of them were able to spread their instigation to terror on platforms provided by Google and specifically its subsidiary YouTube. Finally, Section VII probes YouTube and CSR. It is argued that the Internet is international in character, but it cannot be abused to override law. There is not one law for people and another for the Internet. It is further argued that power without responsibility is dangerous and corrosive.